Short fatigue cracks in intermetallic γ‐TiAl‐alloys. Issue 12 (29th June 2015) - Wessel, W.; Zeismann, F.; Brueckner‐Foit, A.
Abstract: Fatigue crack growth at room temperature and its relation to the local microstructure is studied for four different γ‐TiAl‐alloys with microstructures ranging from coarse and fully lamellar to fine and partly lamellar. It is shown that the number of cycles to failure depends strongly on the efficiency of the first barrier to crack extension, as crack growth rates may increase rapidly once this barrier has been breached by a specific crack. The crack extension behaviour for two typical barriers (colony boundary and twin boundary) is studied using high‐resolution optical and scanning electron microscopy.